2006
DOI: 10.1124/pr.58.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Nomenclature of Nuclear Receptors

Abstract: Abstract--Nuclear receptor pharmacology has, to a certain extent, led the way, compared with other receptor systems, in the appreciation that ligands may exert very diverse pharmacology, based on their individual chemical structure and the allosteric changes induced in the receptor/accessory protein complex. This can lead to very selective pharmacological effects, which may not necessarily be predicted from the experience with other agonists/partial agonists/antagonists. If this is the case, then drug discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
458
0
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 559 publications
(474 citation statements)
references
References 236 publications
(249 reference statements)
2
458
0
14
Order By: Relevance
“…Increasing evidence suggests that the cone gradients are generated during development by the action of diffusible growth factors or hormones (extrinsic signals) and their receptors, mainly nuclear receptor family transcription factors (intrinsic program). These receptors exist as families of related genes that have apparently diverged from a common ancestral precursor (Germain et al, 2006). In the following section, we will focus on recent progress on the role of nuclear receptors in cone development and discuss the possible action of their ligands.…”
Section: Factors For Cone Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that the cone gradients are generated during development by the action of diffusible growth factors or hormones (extrinsic signals) and their receptors, mainly nuclear receptor family transcription factors (intrinsic program). These receptors exist as families of related genes that have apparently diverged from a common ancestral precursor (Germain et al, 2006). In the following section, we will focus on recent progress on the role of nuclear receptors in cone development and discuss the possible action of their ligands.…”
Section: Factors For Cone Developmentmentioning
confidence: 99%
“…Findings from a study designed to map expression quantitative trait loci (eQTL) in the rat showed that point mutations affecting a conserved serine and another residue in the N-terminal domain of Trβ2 (Ser56Asn and His58Arg) correlated with decreases in S-opsin expression levels of as much as 30% in homozygotes (Scheetz et al, 2006). The affected residues fall within a poorly characterized ligand-independent transactivation domain that can interact with cofactors and is the target of post-translational modification in some nuclear receptors (Germain et al, 2006). Trβ2 binds directly to the S-opsin promoter (Figure 3) and has been reported to interact with the basal transcription machinery as well as co-activators and co-repressors to exert complex regulatory effects on target genes (Eckey et al, 2003).…”
Section: Trβ2 Is a Positive Regulator For M-conesmentioning
confidence: 99%
“…So far, 18, 49, and 48 NRs in six subfamilies have been identified in Drosophila melanogaster, mice, and humans, respectively [2][3][4]. TLX, also known as NR2E1 (nuclear receptor subfamily 2, group E, member 1), encodes an orphan NR with no identified ligand.…”
Section: Introductionmentioning
confidence: 99%
“…TR is a TH-regulated transcription factor that belongs to the superfamily of nuclear receptors that plays a central role in various physiological processes as diverse as reproduction, development, and the control of homeostasis (Germain et al, 2006;Gronemeyer et al, 2004;Laudet and Gronemeyer, 2005). In the absence of ligand, the receptor is located on specific response elements in the regulatory regions of target genes and actively inhibits transcription.…”
mentioning
confidence: 99%